The teacher’s suffering within the context of contemporary social change and its clinical-groupal accompaniment (Fractal: Journal of Psychology, 2009)
In this article, the author presents the characteristics of the approach to Group Analysis she has developed based on the reflections of such post-kleinian psychoanalysts as Michael Balint and Wilfred R. Bion ; this conception defines a groupal psychic space for examining suffering in the professional life of the teachers and instructors for whom it has been defined.  Following this presentation, the author will analyze a situation related by Pascal, a philosophy teacher, concerning a moment in one of his courses in which he felt somewhat mistreated by his group of students and, in particular, by one among them.  Group analysis allowed Pascal to relate this scene to key moments in his own personal biography as a student and to begin metabolizing the emotions provoked by the present situation.  The participants in the group thus explore a form of psychic work with formative, professionalizing orientation.